Enhancing EFL Students’ Writing Skills: The Impact of Deepl Translation - Payung, Naftalia Fany; Sukarno, Sukarno (JOLLT Journal of Languages and Language Teaching, 2025)
The integration of the DeepL translation tool as a method to enhance students’ writing skills in EFL classrooms holds great potential. Its capability to provide accurate, context-sensitive translations can aid students in expanding their vocabulary and understanding sentence structures. This study investigated the impact of using DeepL translation on EFL learnersâ€™ writing proficiency through an experimental approach. Two groups of senior high school students participated: an experimental group utilizing DeepL as a writing aid and a control group that did not. Both groups underwent pre-tests and post-tests to evaluate the effectiveness of the intervention. Conducted during the second semester of the 2023/2024 academic year, the quasi-experimental study involved 20 students as subjects. Data collection methods included tests focused on descriptive text writing and a questionnaire to gauge studentsâ€™ responses. Instrument validity and reliability were verified, and the data were analyzed using SPSS 25.0. The findings revealed a significant improvement in the writing skills of students in both groups, indicating that while DeepL translation played a role in enhancing writing proficiency, other factors also contributed. Notably, the experimental group demonstrated a greater improvement compared to the control group, suggesting that DeepL translation provided a unique advantage. However, the results also highlighted the importance of combining digital tools like DeepL with effective teaching strategies to optimize learning outcomes. Overall, the study underscores the value of integrating technology in EFL classrooms while emphasizing the need for a holistic approach to writing instruction.